2022
DOI: 10.1111/ajd.13812
|View full text |Cite
|
Sign up to set email alerts
|

Thalidomide for prevention of camrelizumab‐induced reactive cutaneous capillary endothelial proliferation

Abstract: Objectives:The study evaluated the efficacy of thalidomide in prevention of camrelizumab-induced reactive cutaneous capillary endothelial proliferation (RCCEP).Methods: In this study, patients treated with camrelizumab plus thalidomide or camrelizumab alone were included. The occurrences, onset time, severity of RCCEP and the adverse effect of thalidomide were analysed.Results: A total of 19 patients were enrolled. The incidence of RCCEP in thalidomide group (2/9, 22.2%) was significantly lower than that in ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 28 publications
2
9
0
Order By: Relevance
“…There was no consensus on the optimal dose and therapy duration of thalidomide in the treatment of vascular diseases. Our previous report demonstrated thalidomide response to a low dose 50mg/day in prevention RCCEP [8] , and this study supported the result that low dose thalidomide therapy was an effective option. The most common adverse effect was fatigue, followed by constipation, oedema and rash.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…There was no consensus on the optimal dose and therapy duration of thalidomide in the treatment of vascular diseases. Our previous report demonstrated thalidomide response to a low dose 50mg/day in prevention RCCEP [8] , and this study supported the result that low dose thalidomide therapy was an effective option. The most common adverse effect was fatigue, followed by constipation, oedema and rash.…”
Section: Discussionsupporting
confidence: 86%
“…As an anti-angiogenic agent, apatinib had been used to treat RCCEP [6] , however, the high price and kinds of adverse effects limited its use [7] . As our previous study had shown that thalidomide is effective for prevention the RCCEP [8] , hence, we conducted a retrospective study to compare the clinical benefits of thalidomide and apatinib in prevention the RCCEP in patients receiving camrelizumab therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that irAEs are potentially associated with tumor response in patients receiving immune checkpoint blockade. 20 RCCEP, a special and most common irAE only observed in patients treated with camrelizumab, was a skin lesion manifested as a red spot or nodules that tended to rupture and bleed. 21 Wang et al 22 reported that RCCEP occurrence was positively associated with better mPFS, mOS, and ORR of camrelizumab in patients with advanced hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that irAEs are potentially associated with tumor response in patients receiving immune checkpoint blockade 20 . RCCEP, a special and most common irAE only observed in patients treated with camrelizumab, was a skin lesion manifested as a red spot or nodules that tended to rupture and bleed 21 .…”
Section: Discussionmentioning
confidence: 99%
“… 14 , 15 Carrelizhu-related adverse events (AES) are widely considered as predictive markers for disease control and survival of patients with advanced HCC, especially RCCEP, which has been found in previous studies. 16 , 17 In this study, we tried to investigate the efficacy of TACE combined with carrelizumab in the treatment of advanced HCC, so as to determine the utility of vascular distribution and RCCEP as robust predictors, so as to select the potential benefit patients of TACE combined with carrelizumab according to these factors.…”
Section: Introductionmentioning
confidence: 99%